Ibn Khaldun’s (1332-1406) concept of al-Assabiyya – Obsolete notion or enduring reality? - Yousif, Ahmad (Canadian Federation for the Humanities and Social Sciences, 2009)
The concept of al-Assabiyya which can be translated as kinship, tribal solidarity, commitment, loyalty, blood relationship and identification with one’s own tribe, was coined by Ibn Khaldun during his study of nomadic Arab Bedouin tribes, particularly the Berbers of North Africa. Ibn Khaldun noted that for the Arabs under observation, loyalty to the tribe was of paramount importance, while religious ties were secondary. Nevertheless a change in environment had the potential of generating tyrannical tendencies among those who rule, because they become less dependent on their biological or even ideological kinsmen.